Predatory journals and meetings in forensic sciences: what every expert needs to know about this "parasitic" publishing model - Ricardo Jorge Dinis-Oliveira (Oxford University Press, 2021)
The emergence of the Internet has transformed all areas of society. This includes the universe of scientific publications, with several publishers now exclusively focusing on the electronic format and open access model while expanding to a megajournal scope. In this context, the pandemic of predatory open access journals (POAJs) and meetings are of grave concern to the academic and research community. This new shift within academia produces a variety of new victims; namely, the authors themselves. In turn, scientific knowledge is often discredited, with the public placing less trust in science. Now more than ever, performing research with integrity and selecting a journal in which to publish requires close attention and expertise. The "predatory movement" has developed increasingly sophisticated techniques for misleading people into believing what seem to be credible professional layouts and legitimate invitations. Initiatives such as the Jeffrey Beall's list, the Cabell's Scholarly Analytics and Think.Check.Submit offer some guidance to uncover the "parasitic" intervention of predatory journals and meetings, but specific education in this field is sorely needed. This work aims to review the main characteristics of predatory journals and meetings and to analyze this topic in the context of forensic and legal medicine research.